Epitaxial growth of YBa2Cu3O7 superconducting layers by chemical solution deposition - García, Jorge (2012)
We studied the optimun temperature to favor the epitaxial growth of YBa2Cu3O7 layers using threesintering temperatures of 820, 840 and 860℃, by the chemical solution deposition method in SrTiO3[100] monocrystalline substrates. Surface morphology was obtained by optical imaging, which qualitativelycharacterize the homogeneity and the grain presence along the c-axis. The X-ray diffractionconfirms the preferential epitaxial growth (00l) of the YBa2Cu3O7 crystals, resulting in a higher intensityof the profiles (00l) for the temperature of 860℃. The samples shown superconducting behaviourat critical temperature of 90 K, for the three cases.